2020
DOI: 10.1016/j.tra.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

On the modal shift from motorway to high-speed rail: evidence from Italy

Abstract: Institute of Applied Economics (IREA) in Barcelona was founded in 2005, as a research institute in applied economics. Three consolidated research groups make up the institute: AQR, RISK and GiM, and a large number of members are involved in the Institute. IREA focuses on four priority lines of investigation: (i) the quantitative study of regional and urban economic activity and analysis of regional and local economic policies, (ii) study of public economic activity in markets, particularly in the fields of emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…On the Ankara-Eskisehir route, for example, the number of passengers carried annually has decreased from 208,780 (8%) to 49,275 (2%) (TMTMC, 2013, p. 80). In light of this and other evidence, e.g., Borsati and Albalate (2020) and Givoni and Dobruszkes (2013), it is reasonable to conclude that HSR has contributed to the decline in conventional rail ridership in Turkey since its introduction. On the positive side, this increases the capacity of conventional rail networks for freight trains.…”
Section: Early Results Of Rail Policiesmentioning
confidence: 60%
See 1 more Smart Citation
“…On the Ankara-Eskisehir route, for example, the number of passengers carried annually has decreased from 208,780 (8%) to 49,275 (2%) (TMTMC, 2013, p. 80). In light of this and other evidence, e.g., Borsati and Albalate (2020) and Givoni and Dobruszkes (2013), it is reasonable to conclude that HSR has contributed to the decline in conventional rail ridership in Turkey since its introduction. On the positive side, this increases the capacity of conventional rail networks for freight trains.…”
Section: Early Results Of Rail Policiesmentioning
confidence: 60%
“…Most HSR passengers previously used conventional rail, and mode substitution from aircraft, cars, and coaches to HSR is modest. Borsati and Albalate's (2020) findings show that neither HSR openings nor the opening of on-track competition led to a modal shift from the motorway to HSR services. Conversely, HSR expansion had a slightly positive impact on motorway traffic.…”
Section: Introductionmentioning
confidence: 73%
“…Competitive travel times made possible by the high-speed infrastructure and cheaper fares have led to high-speed services reaching a modal share of over 80% (against aviation below 20%) on the most popular routes in Italy (Milan–Rome), but also in France (Paris–Marseille), where no competition exists yet. However, it has been observed that high-speed services have not attracted a substantial number of private car users in Italy (Borsati & Albalate, 2019), and in France car-pooling is actually detracting passengers from high-speed services.…”
Section: Economic Evaluationmentioning
confidence: 99%
“…Competitive travel times made possible by the high-speed infrastructure and cheaper fares have led to high-speed services reaching a modal share over 80% (against aviation below 20%) on the most popular routes in Italy (Milan-Rome), but also in France (Paris-Marseille), where no competition exists yet. It has been observed, however, that high-speed services have not attracted a substantial number of private car users in Italy (Borsati & Albalate, 2019), and in France car-pooling is actually detracting passengers from high-speed services (Montero, 2019).…”
Section: Future Evolution Of the Marketmentioning
confidence: 99%